Overcoming Gen Z’s FOMO through Kitab Kuning Learning at Islamic Boarding Schools - Ramadhani Firmansyah Wahid; Fihris Fihris; Nasirudin Nasirudin; Aang Kunaepi; Nasikhin Nasikhin (Yayasan Letiges Konsultan Sosial, 2026)
This study aims to analyse the negative impact of Fear of Missing Out (FOMO) on Generation Z's mental resilience and the role of the teachings of the Kitab Kuning in building psychological resilience in the digital age. Using a qualitative case study approach, the research was conducted through unstructured interviews, participant observation, and documents related to the Kitab Kuning, students, teachers, and administrators at the Ma’had of the State Islamic University Walisongo (UIN Walisongo). The data were analysed using the Miles and Huberman model, which involves data reduction, data presentation, drawing conclusions, and verification. The findings indicate that FOMO triggers anxiety, chronic stress, concentration difficulties, reduced self-esteem, and mild depressive symptoms due to social media pressure and unhealthy self-comparison. Additionally, values from the Kitab Kuning—such as contentment (qana’ah), tawakkal (religious commitment), zuhd (asceticism), and muraqabah (compassion)—play a role in supporting spiritual mechanisms to address FOMO, helping maintain inner peace and reduce reliance on external validation. This study makes a positive contribution and can serve as a reference for other Islamic boarding schools. The study is limited by its focus on a single boarding school, so the findings cannot be generalised to other boarding schools that may have different characteristics, backgrounds, or educational systems.